Dual Copper (II) Complex Supported on Diatomite as a Novel and Green Catalyst for the Synthesis of Dihydropyrano[3;2‐b]Chromenediones and Aminopyranopyrans. Issue 37 (1st October 2021) - Davoodi, Elham; Tahanpesar, Elham; Massah, Ahmad Reza
Abstract: Immobilized copper (II) complex, namely, 2, 2′‐((1E, 1′E)‐((6‐(l2‐azaneyl)‐1, 3, 5‐triazine‐2, 4‐diyl)bis(azaneylylidene))bis(methaneylylidene))diphenol, supported on diatomite (Diatomite‐Si‐Pr‐TAT‐Bis‐(AZY‐MY)(Cu)Phenol) was introduced as a robust and heterogeneous catalyst for the synthesis of dihydropyrano[3;2‐b]chromenediones and aminopyranopyrans. The Diatomite‐Si‐Pr‐TAT‐Bis‐(AZY‐MY)(Cu)Phenol catalyst was synthesized by complexation of copper (II) acetate with TAT‐Bis‐(AZY‐MY)Phenol as a ligand with oxygen and nitrogen ligation sites that were anchored on diatomite through 3‐chloropropyltrimethoxysilane. The prepared catalyst was characterized using different microscopic and spectroscopic techniques including SEM, TEM, EDX, XRD, FT‐IR, TGA and ICP. The diatomite is available and cheap support with a high specific surface area and a large amount of hydroxyl group on the surface. A large amount of dual copper (II) complexes were supported on diatomite through covalent bonds. The Diatomite‐Si‐Pr‐TAT‐Bis‐(AZY‐MY)(Cu)Phenol showed good catalytic activity for the synthesis of dihydropyrano[3;2‐b]chromenediones and aminopyranopyrans using aromatic aldehyde, kojic acid, dimedone, or malononitrile. In addition, this catalyst system was reusable for five consecutive catalytic cycles without loss of their catalytic activity. Abstract : Immobilized copper (II) complex, supported on diatomite (Diatomite‐Si‐Pr‐TAT‐Bis‐(AZY‐MY)(Cu)Phenol) was successfully prepared in four steps and introduced as a robust and heterogeneous catalyst for the synthesis of dihydropyrano[3;2‐b]chromenediones and aminopyranopyrans in good to excellent yield and purity under green conditions. The prepared catalyst was characterized using different techniques including SEM, TEM, EDX, XRD, FT‐IR, TGA and ICP. This catalyst was reusable for five consecutive catalytic cycles without loss of catalytic activity. Easy separations and operational simplicity are another significant features of this catalyst.